Bochdalek Hernia - Yuliaji Narendra Putra; Tubagus Odih Rhomdani Wahid; Guntur Surya Alam; Rohadi Rohadi (Program Studi Ilmu Bedah, Fakultas Kedokteran Universitas Udayana, 2018)
Background: Bochdalek hernia is a congenital defect on posterolateral diaphragm with an abnormal connection between the thoracic cavity and the abdominal cavity. This disease causes protrusion of abdominal organs into the thoracic cavity. Case: an 8-day-old baby girl admitted to hospital with shortness of breath 24 hours after delivered. The baby was born spontaneously assisted by midwife. Upon born, the baby was crying strongly and meconium came out 2 hours after birth. On physical examination, the abdomen was inspected flat. Darm contour and darm steifung was observed, and peristaltic sound was heard on left lung. Radiological examination demonstrated a diaphragmatic hernia with ileus obstruction. The patient underwent laparatomy and stomach, ileum, transverse colon, and spleen, was found on foramen Bochdalek. Post-surgery chest X Ray showed favourable result. Ten days after treatment, the patient was discharged in a good condition with no respiratory or digestive problems. After 1 months the patient’s condition remained good and there were no respiratory or digestive complaints. Conclusion: In a rare case like Bochadalek hernia, laparotomy performed as a promising attempt to return the anatomic position of organ.